Expressão e caracterização de um fragmento da glicoproteína e do herpesvírus bovino tipo 1 e uso em um teste sorológico diferencial - Oliveira, Stephan Alberto Machado de (2012)
Bovine herpesvirus type 1 (BoHV-1) is distributed worldwide and produces high economic losses to the in livestock industry. BoHV-1 infection causes respiratory, reproductive and may also be associated with neurological signs. There are several tests that can diagnose the infection, however, serological techniques currently used are not able to differentiate antibodies produced by vaccination from those produced in response to natural infection. What is sought is a mean to differentiate vaccinated animals of those infected by the field strain. Vaccines with deletion in the glycoprotein E (gE) gene have been developed for this purpose. However, this also requires the development of tests capable to differentiate the serological response between infected and vaccinated animals. To this end, a 651 nucleotide fragment corresponding to the amino-terminal third (217 amino acids) of the BoHV-1 gE gene - that shares a high identity with the homologous BoHV-5 counterpart - was cloned as a 6×His-tag fusion protein in an Escherichia coli expression vector pET16b. A soluble protein of approximately 25 kDa was purified from lysates of transformed E. coli. The recombinant protein was detected in Western blot (WB) by anti-6-his tag and anti BoHV-1 gE monoclonal antibodies. Antibodies present in the sera of cattle infected with BoHV-1 and BoHV-5 reacted specifically with the 25 kDa recombinant protein in WB. Moreover, mice immunized with the purified protein developed antibodies that recognized the viral gE in lysates of cell monolayers infected with BoHV-1 and BoHV-5. An indirect ELISA for gE antibodies, based on the expressed protein, was able to differentiate serologically calves vaccinated with a gE-deleted BoHV- 5 strain from calves experimentally infected with BoHV-1 or BoHV-5. These data demonstrate that the antigen retained its immunological properties and, thus, can be used in serological tests for bovine herpesvirus infections. It has a potential use in a indirect ELISA to differentiate naturally infected animals from those vaccinated whit the recombinant, gE-negative strains.